Thermal Analysis for the Dense Granular Target of CIADS - Kang Chen; Yongwei Yang; Yucui Gao (Science and Technology of Nuclear Installations)
For the China Initiative Accelerator Driven System (CIADS), the energy of the protons is 250 MeV, and the current intensity will reach 10 milliamperes. A new concept of a dense granular spallation target is proposed for which the tungsten granules are chosen as the target material. After being bombarded with the accelerated protons from the accelerator, the tungsten granules with high-temperature flow out of the subcritical reactor and the heat is removed by the heat exchanger. One key issue of the target is to remove the 2.5 MW heat deposition safely. Another one is the heat exchange between the target and the subcritical reactor. Based on the model of effective thermal conductivity, a new thermal code is developed in Matlab. The new code is used to calculate the temperature field of the target area near active zone and it is partly verified by commercial CFD code Fluent. The result shows that the peak temperature of the target zone is nearly 740°C and the reactor and the target are proved to be uncoupled in thermal process.